2016
DOI: 10.5194/gmd-9-915-2016
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling methane emission hotspots in boreal peatlands

Abstract: Geosci. Model Dev., 9, 915-926, 2016 www.geosci-model-dev.net/9/915/2016/ doi:10.5194/gmd-9-915-2016 Abstract. Upscaling the properties and effects of small-scale surface heterogeneities to larger scales is a challenging issue in land surface modeling. We developed a novel approach to upscale local methane emissions in a boreal peatland from the micro-topographic scale to the landscape scale. We based this new parameterization on the analysis of the water table pattern generated by the Hummock-Hollow model,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…However, there can also be a lag effect occurring during water-table fluctuations, with higher CH 4 emissions being recorded on water table drawdowns and drought periods and lower fluxes as the water table increases again (Brown et al, 2014). It is incredibly important that interannual variability is taken into account when measuring carbon fluxes, given the large range in annual flux that can occur (e.g., Roulet et al, 2007) in response to variable conditions arising from many sources including localised microtopography (Crestio Aleina, Runkle, Brücher, Kleinen, & Brovkin, 2016), temperature and hydrological regimes (Bubier, Moore, Savage, & Crill, 2005;Waddington et al, 2015), and vegetation cover (Strack et al, 2017;Ström, Mastenapov, & Christensen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, there can also be a lag effect occurring during water-table fluctuations, with higher CH 4 emissions being recorded on water table drawdowns and drought periods and lower fluxes as the water table increases again (Brown et al, 2014). It is incredibly important that interannual variability is taken into account when measuring carbon fluxes, given the large range in annual flux that can occur (e.g., Roulet et al, 2007) in response to variable conditions arising from many sources including localised microtopography (Crestio Aleina, Runkle, Brücher, Kleinen, & Brovkin, 2016), temperature and hydrological regimes (Bubier, Moore, Savage, & Crill, 2005;Waddington et al, 2015), and vegetation cover (Strack et al, 2017;Ström, Mastenapov, & Christensen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We then compared the extent of the wetlands to the inundated fractional area of the model grid cell considered as the corresponding model wet area. It has been recently shown in the literature that the type of vegetation in tundra landscapes is a good indicator of the spatial distribution and variation of CH 4 fluxes (Davidson et al, 2017), and it is also expected that the majority of the CH 4 fluxes are emitted from wetlands in tundra ecosystems (Helbig et al, 2017a). About 26 % of the fluxes measured by the EC tower were emitted from wetland areas within the footprint, i.e., from wet soils with cotton grasses.…”
Section: Eddy Covariance Measurementsmentioning
confidence: 99%
“…CH 4 dynamics in peatlands results from a combination of various biogeochemical processes (Lai, 2009). Controls on CH 4 production, oxidation, and emissions include microtopography (Cresto Aleina et al, 2016), water table depth (Bubier et al, 1995;Granberg et al, 1997), soil temperature (Granberg et al, 1997;Saarnio et al, 1998), substrate quality and availability (Granberg et al, 1997;Segers, 1998;Joabsson et al, 1999), and vegetation cover (Ström et al, 2005;Strack et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing pressures from wildfires across northern peatlands, a knowledge gap still persists on CH 4 emissions after wildfire, especially in boreal regions. In a study on the impact of wildfire on methanotrophic communities from an ombrotrophic peat bog, Danilova et al (2015) found a reduction in the activity of the methanotrophs in burned sites 7 years post-fire. This reduction following wildfire could therefore lead to a potential increase in CH 4 emissions from bog systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation